A comparative evaluation of transcriptome changes in lung and spleen tissues of chickens infected with velogenic and mesogenic Avian Orthoavulavirus 1. (January 2023) - Ul-Rahman, Aziz; Rabani, Masood; Shabbir, Muhammad Zubair
Abstract: Newcastle disease is an acute, highly contagious disease responsible for severe economic losses to the poultry industry worldwide. Clinical assessment of different pathotypes of AOaV-1 strains is well-elucidated in chickens. However, a paucity of data exists for a comparative assessment of avian innate immune responses in birds after infection with two different pathotypes of AOaV-1. We compared early immune responses in chickens infected with a duck-originated velogenic strain (high virulent: genotype VII) and a pigeon-originated mesogenic stain (moderate virulent; genotype VI). Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) identified 4737 differentially expressed genes (DEGs) in the transcriptional profiles of lung and spleen tissues of chickens infected with both pathotypes. More DEGs were expressed in spleen tissue infected with velogenic strain compared to spleen or lung exposed to mesogenic strain. An enriched expression was observed for genes involved in metabolic processes and cellular components, including innate immune-associated signaling pathways. Most DEGs were involved in RIG-I, Toll-like, NF-Kappa B, and MAPK signaling pathways to activate interferon-stimulated genes (ISGs). This study provided a comparative insight into complicated molecular mechanisms and associated DEGs involved in early immune responses of birds to two different AOaV-1 strains. Highlights: Newcastle disease is an acute, highly contagious disease responsible for severe economic losses to the poultry industry. Information on a comparative assessment of avian innate immune responses against varying pathotypes is scarce. Essential analysis identified 4737 DEGs in the transcriptional profiles of lung and spleen tissues of chickens. This study provided a comparative insight into complicated molecular mechanisms and associated DEGs involved in early immune responses of birds.